(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This paper analyses some very interesting aspects of the draft General Comment on the «human right to science», adopted by the UN CESCR, in connection to the CoViD-19 pandemic to underline the role that science can have in emergency situations. These aspects are the right of access to science, the non-discrimination principle, the free dissemination of scientific data and publications.